Original paperEvaluation of the dosimetric impact of loss and displacement of seeds in prostate low-dose-rate brachytherapy - Wang, Yinkun; Nasser, Nicola J.; Borg, Jette; Saibishkumar, Elantholi P. (Journal of Contemporary Brachytherapy, 2015)
Purpose: To analyze the seed loss and displacement and their dosimetric impact in prostate low-dose-rate (LDR) brachytherapy while utilizing the combination of loose and stranded seeds. Material and methods: Two hundred and seventeen prostate cancer patients have been treated with LDR brachytherapy. Loose seeds were implanted in the prostate center and stranded seeds in the periphery of the gland. Patients were imaged with transrectal ultrasound before implant and with computerized tomography/magnetic resonance imaging (CT/MR) one month after implant. The seed loss and displacement had been analyzed. Their impact on prostate dosimetry had been examined. The seed distribution beyond the prostate inferior boundary had been studied. Results: The mean number of seeds per patient that were lost to lung, pelvis/abdomen, urine, or unknown destinations was 0.21, 0.13, 0.03, and 0.29, respectively. Overall, 40.1% of patients had seed loss. Seed migration to lung and pelvis/abdomen occurred in 15.5% and 10.5% of the patients, respectively. Documented seed loss to urine was found in 3% of the patients while 20% of patients had seed loss to unknown destinations. Prostate length difference between pre-plan and post-implant images was within 6 mm in more than 98% of cases. The difference in number of seeds inferior to prostate between pre-plan and post-implant dosimetry was within 7 seeds for 93% of patients. At time of implant, 98% of seeds, inferior to prostate, were within 5 mm and 100% within 15 mm, and in one month post-implant 83% within 9 mm and 96.3% within 15 mm. Prostate post-implant V100, D90, and rectal wall RV100 for patients without seed loss were 94.6%, 113.9%, and 0.98 cm 3 , respectively, as compared to 95.0%, 114.8%, and 0.95 cm 3 for the group with seed loss. Conclusions: Seed loss and displacement have been observed to be frequent. No correlation between seed loss and displacement and post-plan dosimetry has been reported.